Structural, optical, and Raman studies of Gd doped sodium bismuth titanate. Issue 11 (1st August 2018) - Behara, Santosh; Ghatti, Lalitha; Kanthamani, Sivani; Dumpala, Malathi; Thomas, Tiju
Abstract: The effects of gadolinium (Gd) on lead free sodium bismuth titanate (Na0.5 Bi0.5 TiO3, NBT) ceramics are investigated. X-ray diffraction (XRD) studies indicate that perovskite phase (rhombohedral, R3c ) is formed for all Gd doped NBT (Gdx :NBT) compositions (x = 0, 0.02, 0.04, 0.06, 0.08). XRD peak shifts to the higher angles for all compositions except for x = 0.08. Amphoteric nature of Gd in NBT sites are observed i.e., it occupies Bi-site up to x = 0.06 and then distributes to Ti-site. Octahedral distortion (c/a) increases in the range 0.02 ≤ x ≤ 0.06 and then decreases. Raman spectra suggest that the introduction of Gd +3 ion induces structural changes without disturbing the long range order. The material can be readily excited using UV (360 nm) and shows emission peaks at 592 nm and 687 nm. Optical property evaluation indicates that the lowest band gap (Eg = 2.78 eV) is observed at x = 0.08. When x > 0.04, the photoluminescence (PL) intensity decreases indicating the onset of concentration quenching. The critical energy distance (found to be 14 Å) and Dexter's theory based analysis indicate that concentration quenching is attributable to multipole-multipole (specifically dipole-dipole) interactions in the system. Commission International de Eclairage (CIE) chromatic color coordinates are reported for all doped systems; the observed patterns mirror PL analysis results. For instance, PL intensity shrinks beyond 4 at%; this corresponds to a regression in the CIE trajectory with respect to concentration. Highlights: Gd is an amphoteric dopant in NBT; it occupies both A and B sites. Gd substitutes for Bi-site until 6 at%; beyond which Ti gets substituted. Lowest direct bandgap value (Eg = 2.78 eV) is reported for Gdx :NBT at x = 0.08. Concentration-quenching beyond 4 at% is due to dipole-dipole interactions (shown using Dexter's analysis). Critical energy transfer distance in Gd doped NBT is 14 Å.